Using Google Docs for Collaborative Revision in EFL Academic Writing - Tiofanny Elisabet Sirait; Selviana Napitupulu (CV PUTRA PUBLISHER, 2026)
This study explores the use of Google Docs as a collaborative tool to support the revision process in English as a Foreign Language (EFL) academic writing. Employing a qualitative descriptive research design, the study involved six EFL university students enrolled in an academic writing course at a private university in Indonesia. Data were collected through an open-ended questionnaire and analyzed using thematic analysis. The findings reveal that Google Docs facilitated continuous and multi-stage revision through features such as commenting, suggestion mode, and real-time editing. Peer feedback played a central role in shaping students’ revisions, particularly in improving clarity, organization, and language accuracy. Students also perceived several benefits, including increased awareness of writing weaknesses, greater participation, and reduced anxiety during revision. However, challenges such as unclear feedback, unequal participation, and technical issues were also identified. The study concludes that Google Docs supports a process-oriented and interactive approach to revision and has the potential to enhance collaborative academic writing when accompanied by appropriate pedagogical guidance